Analyse Granulometrique et Cartographie des Sediments Superficiels de la Lagune Cotiere au Benin (Afrique de L’Ouest) - Michaël, Tossou Edjrogan; Rodrigue, Adechina Archange; Jéchonias, Hounkpe Bidossèssi; Nelly, Kelome Carine; Aldiouma, Sy Boubou; Tahirou, Diaw Amadou (European Scientific Journal, ESJ, 2019)
The current study is part of the wide-ranging issue related to the sedimentary dynamics of paralic hydro systems. This study aims to characterize the sedimentary cover of the coastal lagoon, one of Benin’s four main water bodies, using the granulometric analysis procedure. Based on shallow sediment samples’, following 48 transects in the lagoon, a few laboratory processes have been undertaken, including granulometry, statistical calculus acting upon the Folk & Ward textural parameters through Excel and Origin 6.0 software, and also sandy feature mapping, while considering the ArcGIS 10.3 software performance. The grain size indexes of these facies indicate a second or poor-rate classification of medium sands, almost symmetrical, with mesokurtic acuity. The Passega diagram describes a saltation or rolling transport of these sands. The combination of Friedman’s, Moiola’s and Weiser’s diagrams reveals fluvial-origin sediments and remobilization from the coastal dune zones flanking the lagoon. At the level of the coastal lagoon, a hydrodynamic zoning is established, characterized by some insubstantial hydro dynamism of the eastern sector, impacted by the influence of the so-called Ouidah lagoon and a relatively strong hydro dynamism of the western sector corresponding to the Grand- Popo lagoon, with a speed ranging between 0.78 to 1.4 m / s towards the bottom and a flow rate of 429 m3 / s, at the Avlo beach station. Ultimately, this study made it possible to underscore the state of hydrodynamic variations observed in the lagoon, notably an opposition between eastern and western sectors, the diversity of sedimentary input sources and the design of the first lithological facies map of this paralic environment, which now stands as a vital tool for its follow-up and monitoring, in the current context of upcoming changes and unremitting alteration. Cette étude s’inscrit dans la problématique de la dynamique sédimentaire des hydrosystèmes paraliques. Elle se base sur les techniques granulométriques pour caractériser les sédiments de la lagune côtière, l’un des quatre principaux plans d’eau paraliques du Bénin. A partir des prélèvements de sédiments superficiels sur 48 transects, des travaux de laboratoire, des calculs de paramètres texturaux de Folk & Ward sur Excel et le logiciel Origin 6.0 ainsi que la cartographie des faciès via ArcGIS 10.3., ont été effectués. Les indices granulométriques de ces faciès indiquent un classement médiocre de sables moyens, presque symétrique, avec une acuité mésocurtique. Le diagramme de Passega décrit un transport par saltation ou roulement de ces sables. La combinaison des diagrammes de Friedman, Moiola et Weiser montre des sédiments d’origine fluviatile et ceux remobilisés à partir des dunes côtières adjacentes à la lagune. Un zonage hydrodynamique est également noté, caractérisé par un hydrodynamisme faible du secteur oriental ou lagune de Ouidah et un hydrodynamisme relativement fort du secteur occidental ou lagune de Grand-Popo, avec une vitesse de l’ordre de 0,78 à 1,4 m/s vers le fond et un débit de 429 m3 /s, à la station de Avlo Plage. En définitive, ce papier fait ressortir l’état de variations hydrodynamiques de la lagune, notamment une opposition entre secteurs oriental et occidental, la diversité des sources d’apports sédimentaires et la réalisation de la première carte des lithofaciès de cet environnement aquatique, outil indispensable à son suivi face à des changements futurs et à un contexte en mutation perpétuelle.